Binding Modes of Teixobactin to Lipid II: Molecular Dynamics Study. Issue 1 (December 2017) - Liu, Yang; Liu, Yaxin; Chan-Park, Mary; Mu, Yuguang
Abstract Teixobactin (TXB) is a newly discovered antibiotic targeting the bacterial cell wall precursor Lipid II (LII ). In the present work, four binding modes of TXB on LII were identified by a contact-map based clustering method. The highly flexible binary complex ensemble was generated by parallel tempering metadynamics simulation in a well-tempered ensemble (PTMetaD-WTE). In agreement with experimental findings, the pyrophosphate group and the attached first sugar subunit of LII are found to be the minimal motif for stable TXB binding. Three of the four binding modes involve the ring structure of TXB and have relatively higher binding affinities, indicating the importance of the ring motif of TXB in LII recognition. TXB-LII complexes with a ratio of 2:1 are also predicted with configurations such that the ring motif of two TXB molecules bound to the pyrophosphate-MurNAc moiety and the glutamic acid residue of one LII, respectively. Our findings disclose that the ring motif of TXB is critical to LII binding and novel antibiotics can be designed based on its mimetics.